Dam stories: Using narrative analysis to understand the debate over water security and the Waimea Community Dam. (17th March 2022) - Lanari, Nora; Overton, John
Abstract: In this article we investigate why environmental debates swing in one direction or another by analysing the discursive construction of water security surrounding the Waimea Community Dam in Aotearoa New Zealand. Using narrative policy analysis based on interview and documentary data, we show how an initial dominant rural water security story was reshaped into a new win‐win‐win metanarrative by absorbing concerns relating to environmental and urban water security. Opposition to the dam, in contrast, failed to gain traction because it did not sufficiently engage with the question of water security, thus increasing uncertainty and paradoxically strengthening the new metanarrative.